Misinformation and mass audiences - Southwell, Brian G. (Brian Glen), 1974-; Thorson, Emily A.; Sheble, Laura (Information (Austin, Tex.), 2018)
Lies and inaccurate information are as old as humanity, but never before have they been so easy to spread. Each moment of every day, the Internet and broadcast media purvey misinformation, either deliberately or accidentally, to a mass audience on subjects ranging from politics to consumer goods to science and medicine, among many others. Because misinformation now has the potential to affect behavior on a massive scale, it is urgently important to understand how it works and what can be done to mitigate its harmful effects. Misinformation and Mass Audiences brings together evidence and ideas from communication research, public health, psychology, political science, environmental studies, and information science to investigate what constitutes misinformation, how it spreads, and how best to counter it. The expert contributors cover such topics as whether and to what extent audiences consciously notice misinformation, the possibilities for audience deception, the ethics of satire in journalism and public affairs programming, the diffusion of rumors, the role of Internet search behavior, and the evolving efforts to counteract misinformation, such as fact-checking programs. The first comprehensive social science volume exploring the prevalence and consequences of, and remedies for, misinformation as a mass communication phenomenon, this will be a crucial resource for students and faculty researching misinformation, policymakers grappling with questions of regulation and prevention, and anyone concerned about this troubling, yet perhaps unavoidable, dimension of current media systems.